Social Media Marketing Effort in Impacting the Intention of Purchase of Green Cosmetics by Indian Consumers - I., Asma Unnisa Begum; Kalpana, R. (International Review of Management and Marketing, 2025)
In the earliest days of civilization, cosmetics evolved with the development of appealing and aesthetic senses. Even people’s perceptions of beauty and fashion have changed over period of time, the demand and craving for cosmetics has not diminished. Indeed, the market for this industry is always expanding. Green cosmetics are nothing but natural cosmetics or personal care products made only with natural ingredients, which stem from plants and minerals. Such cosmetics save the environment, eliminate pollution to a certain extent and ensure the cautious use of non-renewable resources. This research attempts to identify how the variables social media marketing effort and environmental attitude impact the intention towards purchase of Green Cosmetics by Indian female consumers. The role of Brand Attachment has also been examined as a part of this study. Data has been collected from 393 female working professionals from South India. Three states namely Tamilnadu, Karnataka and Kerala have been considered for primary data collection purpose. Stratified sampling is applied to collect the data. Data has been collected in Quantiative form and statistical analysis has been applied on the data. The results of the hypothesis testing using structural equation modelling analysis shows that Environmental attitude creates an impact on the intention of consumers to buy Green Cosmetic Products Online. At the same time, Brand attachment does not moderate the relationship between Environmental Attitude of the consumers and their intention to buy the products.